Incorporation of the Psychoeducational Approach to Educational Management in Residential Care Programs using the Action Research Methodology - Lidia Canquil Silva; Marina Alarcón Espinoza; Alba Zambrano Constanzo (Pontificia Universidad Católica del Perú, 2019)
From an action research it is sought to identify the necessary elements to incorporate the psychoeducational approach to the educational management of a Family Residence in the south of Chile. The qualitative techniques of interviews and participatory diagnostic workshop were used to produce data. The results refer to components of the psychoeducational approach such as, their understanding of the relationship helps, the strategies to use the shared experience and the tools of diagnosis, planning and evaluation, positively influence the educational management of the center. Its incorporation requires a systematic and permanent process over time, as well as the confluence of the presence of criteria and conditions for its appropriation as an approach and intervention methodology by the center's staff.